Observational study on the evolution of systemic treatments for advanced renal cell carcinoma in Southwest Finland between 2010 and 2021 - Hölsä Olivia; Teittinen Kaisa; Anttalainen Anna; Ukkola-Vuoti Liisa; Summanen Milla; Mattila Kalle E. (Sage, 2025)
Background: Novel receptor tyrosine kinase inhibitors and immune checkpoint inhibitors have
been introduced to the treatment of advanced renal cell carcinoma (aRCC) during the past decade.
However, the adoption of novel treatments into clinical practice has been unknown in Finland.
Objectives: Our aim was to evaluate the use of systemic treatments and treatment outcomes
of aRCC patients in Southwest Finland during 2010–2021.
Design and Methods: Clinical characteristics, treatments for aRCC, healthcare resource
utilization, and overall survival (OS) were retrospectively obtained from electronic medical
records. Patients were stratified using the International Metastatic RCC Database Consortium
(IMDC) risk classification.
Results: In total, 1112 RCC patients were identified, 336 (30%) patients presented with aRCC,
and 57% of them (n = 191) had received systemic treatment. Pre-2018, sunitinib (79%) was
the most common first-line treatment, and pazopanib (17%), axitinib (17%), and cabozantinib
(5%) were frequently used in the second-line. Post-2018, sunitinib (52%), cabozantinib (31%),
and the combination of ipilimumab and nivolumab (10%) were most commonly used in the
first-line, and cabozantinib (23%) in the second-line. Median OS for patients with favorable,
intermediate, and poor risk were 61.9, 28.6, and 8.1 months, respectively. A total of 73%, 74%,
and 35% of the patients with favorable, intermediate, and poor risk had received second-line
systemic treatment. In poor-risk patients, the number of hospital inpatient days was twofold
higher compared to intermediate and fourfold higher compared to favorable-risk patients.
Conclusion: New treatment options were readily adopted into routine clinical practice after
becoming reimbursed in Finland. OS and the need for hospitalization depended significantly on
the IMDC risk category. Upfront combination treatments are warranted for poor-risk patients
as the proportion of patients receiving second-line treatment is low.